4. Q4b
Save videos to My Cheatsheet for later, for easy studying.
Video Solution
Q1
Q2
Q3
L1
L2
L3
Similar Question 1
<p>Expand and simplify.</p><p><strong>a)</strong> <code class='latex inline'> \displaystyle (x + 6)^2 </code></p><p><strong>b)</strong> <code class='latex inline'> \displaystyle (k+ 8)^2 </code></p><p><strong>c)</strong> <code class='latex inline'> \displaystyle (p + 7)^2 </code></p>
Similar Question 2
<p>Expand and simplify.</p><p><code class='latex inline'>(c+10)^2</code></p>
Similar Question 3
<p>Expand and simplify.</p><p><code class='latex inline'>(z-3)^2</code></p>
Similar Questions
Learning Path
L1 Quick Intro to Factoring Trinomial with Leading a
L2 Introduction to Factoring ax^2+bx+c
L3 Factoring ax^2+bx+c, ex1
Now You Try
<p>Expand and simplify.</p><p><code class='latex inline'>(8p-7q)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(3a+4b)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(h-9)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(y+4)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(v-12)^2</code></p>
<p>Expand and simplify.</p><p><strong>i)</strong> <code class='latex inline'> \displaystyle (r- 2)^2 </code></p><p><strong>ii)</strong> <code class='latex inline'> \displaystyle (e- 9)^2 </code></p><p><strong>iii)</strong> <code class='latex inline'> \displaystyle (q- 20)^2 </code></p>
<p>Expand and simplify each expression.</p><p><code class='latex inline'>\displaystyle \frac{1}{2}(t -4)^2 </code></p>
<p>Draw a diagram to illustrate each product.</p><p><code class='latex inline'>(x+c)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(t-5)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(p+13)^2</code></p>
<p> Expand the following(don&#39;t guess, exponent symbol means something specific).</p><p><code class='latex inline'> (a - 3b)^2 </code></p>
<p>Expand and simplify. </p><p><code class='latex inline'>(x+3y)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(4g-9h)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(4c-5d)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(a+8)^2</code></p>
<p>Expand and simplify each expression.</p><p><code class='latex inline'>\displaystyle (x+ 2)^2 </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(g+9)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(7u-6w)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(b-100)^2</code></p>
<p>What is the product of <code class='latex inline'>\displaystyle (2 a-3) </code> and <code class='latex inline'>\displaystyle (2 a-3) </code> ? </p><p><code class='latex inline'>\displaystyle \begin{array}{ll}\text { A } 4 a^{2}+12 a+9 & \text { C } 4 a^{2}-12 a-9 \ \text { B } 4 a^{2}+9 & \text { D } 4 a^{2}-12 a+9\end{array} </code></p>
<p> Expand the following using <code class='latex inline'>(a - b)^2 = a^2 - 2ab + b^2</code> short cut.</p><p><code class='latex inline'> (-1 - 2b)^2 </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(x-5)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(n-2)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(r-6)^2</code></p>
<p>Expand and simplify.</p><p> <code class='latex inline'>(m-6)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(k+7)^2</code></p>
<p>Expand and simplify. </p><p><code class='latex inline'>(3a-4b)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(x+5y)^2</code></p>
<p>Expand the following using <code class='latex inline'>(a + b)^2 = a^2 + 2ab + b^2</code> short cut.</p><p><code class='latex inline'>\displaystyle \begin{array}{cccc} &(a) &(a + 2)^2 &(b) &(2c + 2)^2 & &(c)& (1 + 2b)^2 \\ \end{array} </code></p>
<p>Draw a diagram to illustrate each product.</p><p><code class='latex inline'>(x+4)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(b-4)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(w+12)^2</code></p>
<p>A parabola has equation <code class='latex inline'>y=(x+2)^2</code></p><p>Expand and simplify the equation.</p>
<p>Expand and simplify.</p><p><code class='latex inline'>(k-14)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(x-1)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(c-1)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(p-3)(p-3)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(y+3)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(z-3)^2</code></p>
<p>Expand and simplify. </p><p><code class='latex inline'>(9k+2m)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(x+20)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(2x+y)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(6r-8j)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(p-6)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(w+6)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(r-8)^2</code></p>
<p>Expand and simplify. </p><p><code class='latex inline'>(5c+2d)^2</code></p>
<p>Expand and simplify.</p><p><strong>a)</strong> <code class='latex inline'> \displaystyle (x + 6)^2 </code></p><p><strong>b)</strong> <code class='latex inline'> \displaystyle (k+ 8)^2 </code></p><p><strong>c)</strong> <code class='latex inline'> \displaystyle (p + 7)^2 </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(m+5)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(x+5)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(q+7)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(5d+7m)^2</code></p>
<p>Expand and simplify. </p><p> <code class='latex inline'>(2x-y)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(x+4)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(3s-5t)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(e-5)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(4m-n)^2</code></p>
<p> Expand the following using <code class='latex inline'>(a - b)^2 = a^2 - 2ab + b^2</code> short cut.</p><p><code class='latex inline'> (a - 2)^2 </code></p>
<p>Expand and simplify. </p><p><code class='latex inline'>(4u-5v)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(c+10)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(2q+3r)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(n+1)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(n+8)^2</code></p>
<p>Expand and simplify.</p><p> <code class='latex inline'>(x-9)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(z+15)^2</code></p>
<p>A contraction is a shortened form of a word or phrase. The expanded form of the contraction &quot;don&#39;t&quot; is &quot;do not.&quot; You can expand a math phrase by multiplying it out. For example, <code class='latex inline'>\displaystyle (x-2)^{2}=(x-2)(x-2)=x^{2}-4 x+4 </code>. Expand <code class='latex inline'>\displaystyle (2 x+1)^{2} </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(m+11)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(s-11)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(3x+y)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(f-7)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(6p+5q)^2</code></p>
<p> Expand the following using <code class='latex inline'>(a - b)^2 = a^2 - 2ab + b^2</code> short cut.</p><p><code class='latex inline'> (2c - 3)^2 </code></p>
How did you do?
Found an error or missing video? We'll update it within the hour! ðŸ‘‰
Save videos to My Cheatsheet for later, for easy studying.